Variation and inheritance of iron reductase activity in the roots of Common bean (Phaseolus vulgaris L.) and association with seed iron accumulations QTL - Blair, Matthew W.; Knewtson, SJB; Astudillo, Carolina; Li, CM; Fernández, A.C.; Grusak, M.A. (Springer, 2010)
Background: Iron deficiency anemia is a global problem which often affects women and children of developing countries. Strategy I plants, such as common bean (Phaseolus vulgaris L.) take up iron through a process that involves an iron reduction mechanism in their roots; this reduction is required to convert ferric iron to ferrous iron. Root absorbed iron is critical for the iron nutrition of the plant, and for the delivery of iron to the shoot and ultimately the seeds. The objectives of this study were to determine the variability and inheritance for iron reductase activity in a range of genotypes and in a low × high seed iron cross (DOR364 × G19833), to identify quantitative trait loci (QTL) for this trait, and to assess possible associations with seed iron levels.